Premature Mortality from Colorectal Cancer - Ronaldo Valdés Villafranca; Suleidy Pérez García; Ángel Ernesto Ramos Cordero; Suniel Pérez García; Rubén Valdés Villafranca; Elvis Hernández (Revista Finlay, 2020)
Background: colorectal cancer is the third most common form of cancer and the second most important cause of mortality associated with cancer in America. There is a lack of knowledge of the premature mortality behavior from this cause in the Pinar del Río province in the last five years. Objective: to determine the premature mortality tendency from colorectal cancer in Pinar del Río from 2015 to 2019. Method: a retrospective descriptive study was carried out of the total number of prematurely deceased n = 150 due to this neoplasm, for this purpose, the data from the Mortality Registry of the Pinar del Rio Provincial Public Health Department. The variables described were age groups, sex, year of death, municipality of residence and years of life potentially lost. Exploratory data analysis was performed through graphical and mathematical methods of descriptive statistics. Absolute and relative measures were used, as well as summary measures for quantitative and qualitative variables typical of descriptive statistics. Results: the age group 65-69 years (34 %) and the female sex (64 %) were the predominant ones. The mortality linear trend was downward, with the year 2018 being the predominant with 35 cases. The municipality of Pinar del Río stood out with 51 premature deaths and 438 potential years of life lost, however, as an average of years lost, Los Palacios municipality stood out with 13.76 years and the highest risk of dying prematurely corresponded to Guane municipality with 50, 57x100,000 inhabitants. Conclusion: there was a trend towards a decrease in premature mort